The Protective Paradox of Operative Delivery: A Case-Control Analysis of Maternal and Neonatal Risk Factors for Asphyxia in a Balinese Hospital - Ida Ayu Sintya Pratiwi; I Wayan Dharma Artana (Open Access Indonesian Journal of Medical Reviews, 2025)
Neonatal asphyxia constitutes a primary driver of neonatal morbidity and mortality worldwide, with a disproportionate burden in developing nations like Indonesia. The identification of localized, modifiable risk factors is a critical prerequisite for the development of targeted and effective preventive healthcare strategies. This study was designed to meticulously identify the significant maternal, intrapartum, and neonatal risk factors associated with neonatal asphyxia within a tertiary care hospital setting in Bali, Indonesia. We executed a retrospective matched case-control study at a specialized Maternal and Child Hospital in Denpasar, Bali. The study included all neonates diagnosed with asphyxia (cases, n=103) born between January 1st and December 31st, 2023, and 103 randomly selected neonates without asphyxia (controls), also born within the same period. To control for potential confounding, cases and controls were matched by gender and month of birth. An exhaustive review of maternal and neonatal medical records was conducted. The data were analyzed using Chi-square tests for bivariate analysis and a multivariate logistic regression model to isolate the independent predictors of asphyxia. The multivariate analysis identified prematurity as the most profound risk factor for neonatal asphyxia, conferring a more than tenfold increase in risk (Adjusted Odds Ratio [aOR] = 10.33, 95% CI: 4.50-23.71, p<0.001). Significant maternal risk factors included anaemia during pregnancy (aOR = 6.56, 95% CI: 2.36-18.20, p<0.001), maternal age outside the optimal range of 20-35 years (aOR = 3.93, 95% CI: 1.50-10.32, p=0.005), and maternal obesity (aOR = 2.92, 95% CI: 1.20-7.11, p=0.018). Premature rupture of membranes (PROM) was identified as a significant intrapartum risk factor (aOR = 3.16, 95% CI: 1.30-7.72, p=0.011). Notably, delivery by caesarean section or instrumental assistance appeared to be a significant protective factor (aOR = 0.22, 95% CI: 0.08-0.59, p=0.003). In conclusion, prematurity, maternal anaemia, age extremes, maternal obesity, and PROM are confirmed as critical, independent risk factors for neonatal asphyxia in this Balinese population. The striking protective association of operative delivery likely represents a "protective paradox," a statistical artifact arising from confounding by indication, wherein timely and decisive obstetric intervention for high-risk pregnancies successfully mitigates adverse outcomes. Preventive strategies must therefore be multifaceted, prioritizing the public health imperatives of preterm birth prevention and the rigorous clinical management of maternal anaemia and obesity throughout the continuum of antenatal care.